Implementasi Folium pada Hasil Klaster Diabetes Mellitus di Puskesmas Modopuro - Yovan Febriawan Nurpratama; Dhian Satria Yudha Kartika; Reisa Permatasari (Jurnal Ilmiah Teknik Informatika dan Komunikasi, 2023)
Puskesmas is a public facility that provides health services to the community, including in remote areas. In the era of health technology, Electronic Medical Records (RME) have facilitated community access to health services, as is the case at the Modopuro Health Center. RME allows the identification of common diseases, including diabetes mellitus, which has two types. However, there is no cluster visualization of RME data from January to April 2023 that can reveal the distribution pattern of this disease. In this study, diabetes mellitus clusters were visualized using python and folium library. Patient coordinates were used in the visualization, with Modopuro Health Center as the starting point of the map. The visualization results are displayed on a map with cluster selection features. The more diverse the colors and markers in an area, the more people who suffer from the disease. The highest cluster 0 population is located in Kebondalem Village, the highest cluster 1 population is located in Pekukuhan Village, the highest cluster 2 population is located in Modopuro Village, the highest cluster 3 population is located in Ngimbangan Village, and the highest cluster 4 population is located in Modopuro Village.